PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Diptarina Yasmeen; Sri Hermawati (Universitas Gunadarma, 2015)
This study describes the corporate governance linking between the various participants in the company who determine the direction of the company's performance: This study aims to determine the effect of good corporate governance to the quality of financial reporting in manufacturing companies. Good Corporate Governance is measured from institutional ownership, managerial ownership and the board of commissioners and supporting variables such as firm age (Age) and leverage enterprise and financial reporting quality is measured through a questionnaire distributed by 65 respondents. The statistical method used is a simple linear regression analysis. Sample research is a manufacturing company in 2012. Based on the results of hypothesis testing can be concluded that the leverage effect on the Quality of Financial Reporting; while BOC, Institutional Ownership, Managerial Ownership and firm age (Age) does not affect the quality of financial reporting. Keywords: BOC, Managerial Ownership, Leverage, Age, Quality of Financial Reporting